Leadership characteristics needed by perum bulog in order to change from dominantly public service obligation company to become dominantly commercial company - Mahardhika, Gemilang Ihza; Lantu, Donald Crestofel (Journal of Business and Management, 2019)
Bulog is a state-owned enterprise that operates in the field of food. Bulog has three general functions, namely maintaining food price stability, ensuring food availability, and ensuring food affordability. Although as a state-owned company, Bulog does not entirely run a profit-oriented commercial business but rather tends to carry out a public service function where Bulog must distribute food aid from the government to the poor.However, along with the issuance of Presidential Regulation No.63 of 2017 which decides that food aid from the government is no longer fully controlled by the National Logistics Agency but is left to the free market mechanism. This is a challenge for Bulog, because they must turn to be more commercial than public service, and must be more competitive and reduce the role of public services in facing this challenge, it requires progressive changes in Bulog, one of which is a change in the field of leadership.Through a semi-structured interview method with several Bulog employees, the researcher identified the leadership characteristics needed by Bulog to face the challenges of being a more profit-oriented company. Also, this study also discusses the forms of implementation that have been carried out by Bulog in changing the character of leadership to face the challenges it faces. The researcher found several leadership characteristics for Bulog such as being open-minded, reliable, able to see business opportunities carefully, customer-oriented, and disciplined. In addition, in terms of implementation, Bulog has issued Directors' Regulation Number 05 Year 2019 regarding the Managerial Competency Dictionary which is issued as a character reference that must be possessed by Bulog to face challenging and dynamic business situations.Keywords: Bulog, characteritics, leadership PSO, profit oriented, challenge